DỊ THƯỜNG VÀ BIẾN THIÊN THEO MÙA CỦA DÒNG ĐIỆN XÍCH ĐẠO - Thanh, Lê Trường; Minh, Lê Huy; Châu, Hà Duyên; VAFI, DOUMOUYA; COHEN, YVES (Vietnam Journal of Earth Sciences, 2011)
Anomaly of equatorial electrojet (EEJ) and its seasonal variation In this paper we apply the new technique to separate the effect of the EEJ with the magnetic data received on CHAMP satellite from 2002 to 2007 to study the anomaly of the EEJ and its season variation in global scale. We found that: In summer and equinox, along the magnetic equator there are 4 maximum peaks and 4 minima of the current density of the EEJ. These maximum peaks are at the longitudes: 105οE, 0ο, 90οW and 180οW, among which the peak at the Vietnamese sector (105οE) is maximal. These minima are at the longitudes 45οE, 140οE, 40οW and 135οW. In winter, the EEJ have only 3 peaks at 135οW, 10οW, and 100οE. The peak at 135οW is maximal. The current density of the EEJ is maximum in the equinox, smaller in the summer and smallest in the winter. In the period when the Sun is active, the current density of the EEJ is bigger than that in the calm period of the Sun. Additionally, these results are compared with those obtained from the magnetic data received at the 3 observatories pairs on the Earth’s surface with one of the observatories in the immediate proximity to the dip-equator (HUA, AAE, BCL) and the other outside of the EEJ footprint area (FUQ, QSB, PHU) for consolidating the well-founded properties and the magnetic data received on CHAMP are very useful to study the EEJ in Vietnam and over the world